EFEKTIVITAS PENGATURAN PAJAK PENGHASILAN TERHADAP PERILAKU USAHA EKONOMI DIGITAL LINTAS NEGARA DI INDONESIA - Edward Parulian Donald Tua Immanuel S; Sudarto (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
The rapid transformation of Indonesia’s digital economy has contributed significantly to national economic growth, yet it poses major challenges to the country’s taxation system, particularly in addressing cross-border digital transactions. Global digital companies such as Google, Facebook, and Netflix generate substantial income from the Indonesian market without establishing sufficient physical presence to be classified as a Permanent Establishment (PE) under conventional tax principles. In response, Indonesia introduced income tax and electronic transaction tax regulations through Government Regulation in Lieu of Law (PERPU) No. 1 of 2020. However, the implementation remains ineffective due to regulatory gaps, incompatibility with Double Taxation Avoidance Agreements (DTAAs), and the absence of detailed technical guidelines. This study employs a normative juridical method to assess the effectiveness of income tax regulation on cross-border digital economy activities, referencing OECD principles and Indonesia’s legislative drafting standards. The findings reveal that current tax policies do not fully meet the criteria of being enforceable and effective. Therefore, regulatory refinement is necessary to close tax avoidance loopholes and enhance the fiscal contribution of the digital sector.